Claims on Housing Space in Nineteenth-Century Montreal - Gilliland, Jason; Olson, Sherry (Urban History Review / Revue d'histoire urbaine, 1998)
Space per person is a fundamental measure of equity in an urban society. From small samples of the Montreal population over the years 1861–1901, we infer substantial improvement in the average dwelling space available per person, but an extreme and persistent inequity in the distribution among households. The housing market remained polarised in terms of class and cultural identity. As crowding diminished, urban density increased, and the problem of working-class housing became, increasingly, one of collective rather than individual space. Families, through networks of kinship and neighbouring, found new ways to exert some control over vital urban micro-spaces. In a continuous, demanding process of adjustment of households to dwellings, the re-structuring of households was a factor as important as their moves from house to house.